2017
DOI: 10.1002/14651858.cd011821.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antiseptics for burns

Abstract: It was often uncertain whether antiseptics were associated with any difference in healing, infections, or other outcomes. Where there is moderate or high certainty evidence, decision makers need to consider the applicability of the evidence from the comparison to their patients. Reporting was poor, to the extent that we are not confident that most trials are free from risk of bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
58
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 99 publications
1
58
0
9
Order By: Relevance
“…Numerous randomized controlled clinical studies and case reports have been conducted in order to prove its wound-healing efficacy. A meta-analysis investigating the efficacy of honey in different types of wounds indicated that the relative effect of honey on wounds was unclear because the trials performed so far have been small, clinically heterogeneous, short, and highly biased [1][2][3][4][5]. However, some systematic reviews and meta-analyses have indicated that honey dressings are superior in the treatment of diabetic foot ulcers or burns when compared to conventional dressings [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous randomized controlled clinical studies and case reports have been conducted in order to prove its wound-healing efficacy. A meta-analysis investigating the efficacy of honey in different types of wounds indicated that the relative effect of honey on wounds was unclear because the trials performed so far have been small, clinically heterogeneous, short, and highly biased [1][2][3][4][5]. However, some systematic reviews and meta-analyses have indicated that honey dressings are superior in the treatment of diabetic foot ulcers or burns when compared to conventional dressings [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Aloe extracts are used in a wide variety of medicinal and cosmetic products marketed for skin healing, and numerous patents cover the use of acetylated mannans from Aloe vera due to their supposed immunomodulatory effects (45,46). However, two recent Cochrane reviews found that published studies on the wound healing and antiseptic properties of this plant were generally of low quality and that the results of human trials that have been published returned variable results, spanning from help and harm to the patients (47,48). The available literature on the biological composition and activity of mastic was even less clear.…”
Section: Results and Discussion Network Analysis Of Remedies For Skinmentioning
confidence: 99%
“…while the most potent medical-grade honey (manuka honey) also contains highly active compounds from the plant from which it is made, a range of European honeys have been shown to have measurable antimicrobial effects in vitro (74)(75)(76)(77). Cochrane reviews found moderate to good evidence that honey reduces healing times for burns and surgical wounds (48,78) and weak evidence that honey helps to prevent mouth ulcers in cancer patients (79), and another Cochrane review suggested that honey may be better than no treatment or placebo in relieving childhood cough (80).…”
Section: Results and Discussion Network Analysis Of Remedies For Skinmentioning
confidence: 99%
“…The effect of the treatment on wound healing was studied macroscopically and using histology. In terms of reduction of wound bacterial counts the NPWT was compared to topical silver sulfadiazine cream which is commonly used antimicrobial in burn care …”
Section: Introductionmentioning
confidence: 99%